2000
DOI: 10.1021/ja992350v
|View full text |Cite
|
Sign up to set email alerts
|

Toward Nanodevices:  Synthesis and Characterization of the Nanoporous Surfactant-Encapsulated Keplerate (DODA)40(NH4)2[(H2O)n⊂Mo132O372(CH3COO)30(H2O)72]

Abstract: We describe the spontaneous self-assembly and the superstructure of a discrete surfactant-encapsulated cluster, (DODA) 40 (NH 4 ) 2 [(H 2 O) n ⊂Mo 132 O 372 (CH 3 COO) 30 (H 2 O) 72 ] (2, n ≈ 50), which consists of a hollow giant isopolyoxomolybdate core covered by a hydrophobic shell of dimethyldioctadecylammonium (DODA) cations. The structural characterization of these nanoporous core-shell particles is based on small-angle X-ray scattering (SAXS) data on solutions of the encapsulated clusters, TEM investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
139
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 244 publications
(147 citation statements)
references
References 18 publications
6
139
0
2
Order By: Relevance
“…Our simulations confirmed that DODA molecules, starting from a random distribution, would aggregate to form a steady-state hydrophobic spheroid. In accord to previous modeling work [133] on a porous CH 3 COO-linker nanocapsule (the total charge of which is −42e), the concentration of DODA was observed to decrease with the radial distance from the capsule's surface. In our case, the total charge of the capsule-DODA spheroid varied from −2 to −10e in the steady state.…”
Section: Chaptersupporting
confidence: 88%
See 1 more Smart Citation
“…Our simulations confirmed that DODA molecules, starting from a random distribution, would aggregate to form a steady-state hydrophobic spheroid. In accord to previous modeling work [133] on a porous CH 3 COO-linker nanocapsule (the total charge of which is −42e), the concentration of DODA was observed to decrease with the radial distance from the capsule's surface. In our case, the total charge of the capsule-DODA spheroid varied from −2 to −10e in the steady state.…”
Section: Chaptersupporting
confidence: 88%
“…It was previously shown that such porous nanocapsules can be encapsulated with dimethyldioctadecylammonium (DODA) surfactants, amphiphilic cations consisting of a cationic ammonium group attached to two long nonpolar tails [133,127].…”
Section: Chaptermentioning
confidence: 99%
“…This preparation scheme permits characterization of the materials brought into use at each step. Besides alkylammonium compounds, this approach has also been successfully used to encapsulate POMs with dendritically branching amphiphiles [73][74][75][76]. These results show that surfactant-encapsulation is widely applicable to different POM clusters and amphiphilic systems.…”
Section: Surfactant-encapsulated Pom Clustermentioning
confidence: 87%
“…7) [74,75]. Based on elemental analysis, 40 DODA molecules encapsulate the cluster, leading to a discrete, nearly spherical particle with a molecular mass of approximately 43.900 g/mol.…”
Section: Structural Characterization Of Secsmentioning
confidence: 99%
“…The POMs can also self-assemble into ordered patterns at the nanometer scale, and thus have multilevel ordered structures [120,121]. The great diversity in composition and structure of POMs make them attractive materials in many fields [122].…”
Section: Self-assembly Of Polyoxometalate Nanoparticlesmentioning
confidence: 99%